PENGARUH APLIKASI Trichoderma sp. TERHADAP LAYU BAKTERI Ralstonia solanacearum PADA TANAMAN PISANG - Trisnawati, Eka; Panggeso, Johanis; Asrul, Asrul (AGROTEKBIS, 2019)
Banana plant (Musa paradisiacal L.) is one of Indonesia native plants currently facing a serious problem of bacterial wilt disease caused by Ralstonia solanacearum bacteria. The purpose of this research was to determine the effect of Trichoderma sp. application at different rates to controll the bacterial. This research was conducted in the Plant Disease Laboratory and in the Agricultural Faculty of Agriculture, Tadulako University from April to September 2017. Banana seeds used were four month old kepok. This study used a Completely Randomized Design (CRD) with four rates of Trichoderma sp. i.e. control (T0), 20 g (T1), 40 g (T2), and 60 g (T3). Each treatment was replicated five times. The results of this study showed that the fastest incubation period occurred in T0 treatment (7 days) compared to the lowest T3 (25 days). The T3 treatment was able to reduce the bacterial wilting attack by 10-20%.